THE ACCURACY OF QIBLA DIRECTION OF CEMETERIES USING MODERN QIBLA TOOLS - Jasmin, Suriah Pebriyani; Anas, Ashar; Sari, Muspita; Mangenre, Muh. Fadli; S., LD Dian Hidayat (Jurnal Al-Dustur, 2023)
It is important to determine the Qibla direction accurately, because it is a requirement for the validity of prayer and this article discusses the Qibla direction of cemeteries, especially in Bone District, by taking direct measurement at the location of the cemetery. This is a field research which is oriented to several cemeteries in Bone District using qualitative descriptive analysis and multi-approaches, namely normative theological, sociological, historical, and modern technological approaches. The data collected through this research were obtained from direct observation at several public cemeteries in Bone District and documentation during the observation. The results show that the direction of the cemeteries at the research sites is different, so it can be concluded that the measurement of the Qibla direction at these locations still uses the classical method, such as following the direction where the sun sets in the evening and looking for clues through the stars at night to determine the Qibla direction, although those methods are still just an estimate due to the lack of public understanding of measuring the Qibla direction. From this research, the researchers hope that people will understand more about the Qibla direction, not only based on the place where the sun sets, but also determine the Qibla using astronomical tools, both manual and modern. In this way, the astronomical science will further develop and the issue of Qibla will no longer be a matter of debate, because it uses proper knowledge.